2022
DOI: 10.3390/machines10060462
|View full text |Cite
|
Sign up to set email alerts
|

Rotor Strength Analysis of FeCo-Based Permanent Magnet High Speed Motor

Abstract: To solve the problem of tension stress caused by centrifugal force and caused by high-speed operation of permanent magnet (PM) rotor, a FeCo-based PM rotor structure model is proposed. Based on the thick-walled cylinder theory, the uniform analytical calculation formulas of strain field, displacement field, and stress field of high-speed permanent magnet rotor are derived, and the stresses of FeCo-based PM and sleeve are obtained. The correctness of analytical calculation method (ACM) is verified by finite ele… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Figure 8a shows that the eddy current is reduced more than other tapering numbers from T n = 14 to T n = 18. In the range of T n (10)(11)(12)(13)(19)(20)(21)(22)(23)(24), it was confirmed that the effect on the tapering model was not significantly affected when considering the number of slots. Figure 8b shows the minimum safety factor through mechanical stiffness analysis for each parameter.…”
Section: Selecting the Optimal Sleeve Tapering Modelmentioning
confidence: 74%
See 1 more Smart Citation
“…Figure 8a shows that the eddy current is reduced more than other tapering numbers from T n = 14 to T n = 18. In the range of T n (10)(11)(12)(13)(19)(20)(21)(22)(23)(24), it was confirmed that the effect on the tapering model was not significantly affected when considering the number of slots. Figure 8b shows the minimum safety factor through mechanical stiffness analysis for each parameter.…”
Section: Selecting the Optimal Sleeve Tapering Modelmentioning
confidence: 74%
“…As a result, the equivalent stress derived by equating the directional stress state to a scalar amount is used to assess the structure's safety. This equivalent stress is also referred to as von Mises stress [24], and is equivalent to a uniaxial tensile or compressive stress of a composite load from multiple directions. The expression for this is:…”
Section: Rotor Stress and Minimum Safety Factormentioning
confidence: 99%
“…The average UMF values of the investigated machines are also listed in It should be noted amount of UMF in any given electric machine can lead to unwanted vibration and noise in such machine and this is similar to the effect of torque pulsation (Sung et al, 2013) and (Shi et al, 2020). Moreover, the noise and vibration levels in an electric machine would be a function of the adopted magnetic core materials, as established in Hou et al, (2022). Furthermore, negative effect of magnetic forces could also be felt on the stator especially around its teeth; however, the magnitude of this effect can be reduced by adopting appropriate winding topology through improved winding factors (Farshadnia et al, 2018).…”
Section: Statements and Declarationsmentioning
confidence: 96%
“…Conversely, the e-motor with the smallest magnet surface to generate active magnetic flux produced the lowest torque. Moreover, variations in magnet dimensions from tolerances affect the mechanical integrity and strength of the rotor structure, limiting the maximum safe operating speed [38].…”
Section: Rotor Magnet Parametersmentioning
confidence: 99%